What is the effect of ankle disk training and taping on proprioception deficit after lateral ankle sprains among active populations? – A systematic review. (July 2022) - Otsuka, Shoko; Papadopoulos, Konstantinos; Bampouras, Theodoros M.; Maestroni, Luca
Abstract: Objective: To investigate the effect of disk training and tape application on diminished proprioception after Lateral Ankle Sprain (LAS) in active populations. Eligibility criteria: Only clinical trials investigating the effectiveness of disk training and ankle tape on proprioception deficits following LAS by assessing JPS or kinaesthesia were included. Information sources: Electronic databases of PubMed, MEDLINE, SPORTDiscus, CINAHL, Web of Science, Cochrane and PEDro were searched. The main search was conducted in February 2022. Risk of bias: The physiotherapy Evidence Database (PEDro) scale was utilised to assess the methodological quality of each article. Result: The search yielded six studies investigating the effects of disk training and four studies investigating the effects of inelastic tape. Five articles showed a significant improvement on JPS after disk training. However, no difference across different intervention groups was observed in one study. Only one trial presented an immediate significant improvement when taped, while another study showed that external ankle supports significantly improved JPS after 2 weeks and after 2 months. Three of four studies found no immediate improvement on proprioceptive deficits by the use of tape. Conclusions: This review found that disk training may improve impaired proprioception after LAS, whilst the efficacy of inelastic tape was not evident due to methodological quality of the few available studies. Further studies are needed to establish whether these interventions can be used clinically with sufficient evidence.